Literature Study: Cortisol Hormone to DHEA-S Ratio as an Indicator of HPA Axis Activity in Chronic Stress and Insulin Resistance - Sinaga, Odor Debora Pita Uli; Gultom, Febry Yeni; Sihite, Judika Adventist Maleakhi; Solin, Naomi Putri Chelsea; Silitonga, Melva (AR-RUMMAN: Journal of Education and Learning Evaluation, 2025)
Chronic stress can disrupt the regulation of the Hypothalamic-Pituitary-Adrenal (HPA) axis, causing dysregulation of cortisol secretion and an imbalance in the ratio of cortisol to dehydroepiandrosterone sulfate (DHEA-S), which is implicated in the development of insulin resistance and Type 2 Diabetes Mellitus (T2DM). Cortisol, as an insulin antagonist, increases hepatic glucose production and reduces peripheral glucose uptake, while DHEA-S has a protective effect on glucose metabolism. This literature review aims to evaluate the evidence related to the role of the cortisol/DHEA-S ratio as a potential biomarker in the relationship between chronic stress and insulin resistance. The method used is a critical synthesis of previous studies on the mechanism of the HPA axis, the impact of stress on glucose metabolism, and the clinical significance of the cortisol/DHEA-S ratio. The results of the analysis indicate that an imbalance in the cortisol/DHEA-S ratio due to chronic stress contributes to impaired insulin sensitivity, reinforcing the importance of this biomarker approach in the management of T2DM risk. This study highlights the need for further research to validate the use of the cortisol/DHEA-S ratio as a predictive tool and therapeutic intervention.